The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1055/s-0037-1610329
|View full text |Cite
|
Sign up to set email alerts
|

Acyl Radical Chemistry via Visible-Light Photoredox Catalysis

Abstract: Visible light photoredox catalysis has enabled easy access to acyl radicals under mild reaction conditions. Reactive acyl radicals, generated from various acyl precursors such as aldehydes, α-ketoacids, carboxylic acids, anhydrides, acyl thioesters, acyl chlorides, or acyl silanes, can undergo a diverse range of synthetically useful transformations, which were previously difficult or inaccessible. This review summarizes such recent progress of visible-light-driven acyl radical generation using transition metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(72 citation statements)
references
References 118 publications
1
71
0
Order By: Relevance
“…In pathway A , carboxylic acid 13 could simply be formed by a dark autoxidation of aldehyde 11 in the presence of oxygen via radical photoinitiation (Scheme ) . The resulting acyl radical could efficiently couple with ground‐state oxygen to form peroxy acid 18 , which would react with another molecule of aldehyde and rearrange to give a Criegee‐like intermediate, which disproportionates into two molecules of acid 13 . Our previous work suggested that pyronin‐9‐carboxylates, analogous to xanthene‐9‐carboxylic acid, could release carbon monoxide (CO) upon irradiation via a putative α‐lactone intermediate ( 19 , Scheme ), observed, for example, in atmospheric photochemistry of methacrolein .…”
Section: Resultsmentioning
confidence: 99%
“…In pathway A , carboxylic acid 13 could simply be formed by a dark autoxidation of aldehyde 11 in the presence of oxygen via radical photoinitiation (Scheme ) . The resulting acyl radical could efficiently couple with ground‐state oxygen to form peroxy acid 18 , which would react with another molecule of aldehyde and rearrange to give a Criegee‐like intermediate, which disproportionates into two molecules of acid 13 . Our previous work suggested that pyronin‐9‐carboxylates, analogous to xanthene‐9‐carboxylic acid, could release carbon monoxide (CO) upon irradiation via a putative α‐lactone intermediate ( 19 , Scheme ), observed, for example, in atmospheric photochemistry of methacrolein .…”
Section: Resultsmentioning
confidence: 99%
“…When Az‐6 was employed instead of Az‐1 , modest enantioselectivity was observed (Scheme ). To the best of our knowledge, this preliminary result is a novel enantioselective acyl‐like radical–radical coupling for the formation of ketones bearing an α‐stereogenic center, thus differentiating this work from other acyl radical processes . Efforts to increase the selectivity and scope of this process are currently underway.…”
Section: Methodsmentioning
confidence: 92%
“…). However, carboxylic acid‐derived acyl radicals have primarily been employed in Giese‐type additions to activated alkenes . Limited reports describe the coupling of an acyl radical with an alkyl radical, thus presenting an opportunity to explore and develop new reactivity.…”
Section: Methodsmentioning
confidence: 99%
“…In a similar way, some transformations currently seem very challenging via an electrochemical approach. Examples are the usage of carbazoles due to electropolymerization (Section 2.4) [84,88,89,90,91] and the difficulty of employing aldehydes as acyl radical precursors [3] compared to the photochemical approach [198].…”
Section: Discussionmentioning
confidence: 99%